Complaint Handling, Customisation & Service Quality- Impact on Customer loyalty in Mobile services, India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Worldwide, telecom services have been recognized as an important tool for a nation's socio-economic development, and thus telecom infrastructure is treated as a crucial factor in achieving socio-economic goals in India also. But telecom service providers are facing a huge competition and involving in mergers. To survive in this scenario service providers should look into customer loyalty for designing and delivering services to attract and retain customer. This paper highlights the importance of the same by studying the impact of three factors namely service quality, personalisation and complaint handling in mobile services. 414 respondent’s data were collected by the help of well-designed questionnaire and SEM analysis was performed to validate the model. The findings of the study revealed that in the three factors service quality is having major impact on loyalty then personalisation and next complaint handling. And the model is a good fit for the constructs. The paper consists of conclusion and implications of the study.